Fumonisin B1 Exposure Causes Intestinal Tissue Damage by Triggering Oxidative Stress Pathways and Inducing Associated CYP Isoenzymes - Changyu Cao; Weiping Hua; Runxi Xian; Yang Liu (Toxins)
Fumonisin B1 (FB1) is considered the most toxic fumonisin produced by fungi and is commonly found in contaminated feed and crops. Fumonisin and its metabolites extensively exist in feed and crops, where FB1-polluted crop ingestion can do harm to livestock and poultry, causing poultry intestinal toxicity in the latter. For investigating FB1-mediated intestinal toxicity, we assessed the function of FB1 exposure in quail intestines and explored its possible molecular mechanisms. In total, 120 quail pups were classified into two groups, where those in the control group were given a typical control diet, and those in the experimental group were given a typical diet that contained 30 mg/kg FB1. We evaluated the histopathological and ultrastructural changes in quails’ intestines on days 14, 28, and 42, and studied the molecular mechanisms by assessing oxidative stress, inflammation, and nuclear xenobiotic receptors (NXRs). Our results suggest that FB1 exposure causes intestinal inflammation by triggering oxidative stress pathways and modulating NXRs to induce Cytochrome P450 proteins (CYP) isoforms, leading to intestinal histopathological damage. The results of this study shed novel light on the molecular mechanism underlying FB1-induced intestinal injury in juvenile quails.